(3QSGdI aj hba MeRI hgTGes - (3Ydj Hf YKeGf Hf eMeO Hf CMeO, CHh GdHbGA GdYPQj, hjYQa H (B: (3GHf GdbGUM,J (B801 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeg hjcGaF eRjOg hHYO agPg eSGFd ai ePGgH MeRI hgTGe UMJ ai GdfTQ hZjQg ef ZjQ Jhba hdG JVYja s
(3BNQgG (B:s
(3hcPdc eY GdeO hGdbUQ CjVkG agPg eSGFd MeRI hgTGe bS YdjgG eG hbY ef fXGFQgG abO HGdZJ ai JHjfgG QGLjkG KhGH Gddg JYGdi hgh MSHi hfYe Gdhcjd hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hGdahGJM HGdMeQIs
(3HBNQgG eWGdYI ai bQGAGJ dhQT hahGFO s
(3fSNI ecQQI hdcfgG CaVd ef GdSGHbI s
(3bQf GdfSN (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs